Mathematical Model for Transmission and Control of Tuberculosis in Humans. - Niringiyimana, Innocent (Kabale University, 2024)
Despite all efforts to curb and exterminate the menace of Tuberculosis (TB) epidemics in the human population, the disease remains one of the major causes of death, with one–third of the world’s population infected. In this project, we study a deterministic mathematical model to have a better insight in the transmission dynamics of TB. The model is shown to have a disease-free equilibrium, E0, and its local stability is established using the basic reproduction number, Ro. If Ro < 1, the infection can be controlled and then eradicated and when Ro > 1, the disease will persist.